Learning through games using multimedia courseware for primary school students - Ab Wahab, Siti Farahiyah (Universiti Teknologi Petronas, 2006)
This project presents a preliminary work on examining the importance of incorporating the elements of games, in particular complex games, in the design of an interactive multimedia-learningenvironment to enhance and create an engaging learning experience. A review suggests that computer games have the potential to enhance the learning environment; in part due to its interactive and engagement attributes. The result of an informal survey reveals that "Fraction", one of the mathematic topics taught at schools was identified as one of the most difficult topics to teach. Thus development of the prototype software was based on this topic. An initial examination of two current multimedia courseware CDs used for Mathematic Year 3 under this topic has revealed that most of the contents in the CDs have integrated all the multimedia elements such as text, image, audio and graphics but it lacks interactive games and activities that could stimulate enjoyment and motivation for learning. Activities found consist mainly of simpleor trivial gamesthat do not lend to sustainedengagement. The architecture and the preliminary designof the prototype software that integrate complexgames are described. To form the basis of the courseware development, a pre-survey questionnaire was conducted to find out students interest on computer games. The results of the survey showed that 100% or 60 out of 60 respondent express interest and engage on games. The result of the analysis provides motivations for the development of the learning through games courseware. The development of the courseware is based on the courseware development framework which will analyze the requirement and courseware specification, the initial storyboard, designation of multimedia, the integration of the storyboard and the design itself and also the testing on the courseware. The result of testing on the courseware shows that by integrating complex games elements and multimedia elements on courseware may help students understand and motivate them to learn. In conclusion, a courseware with additional games elements could be an interactive and more interesting usable courseware.